Pengaruh Media Pembelajaran Puzzle Edukatif Terhadap Kemampuan Kognitif Peserta Didik Materi Aturan Sekolahku Kelas III SD Negeri Menanggal 601 Surabaya - Klara Arka Dina, Hana; Mahya Fanny, Arif (Universitas Jambi, 2025)
This study aims to determine the effect of educational puzzle learning media on students' cognitive abilities on school rules material in class III SD Negeri Menanggal 601 Surabaya. The lack of use of concrete media in learning causes students to feel bored and less active, thus having an impact on their cognitive abilities. Educational puzzles as an interesting and fun learning media can help students remember the material better and improve focus, problem solving, and decision making. This study used a quantitative approach with a quasi-experimental design, namely a non-equivalent control group design. The research sample was third grade students who were selected using the probability method with simple random sampling technique. Data were collected through tests and analyzed using t-test. The results showed a significant difference between the experimental group that used educational puzzles and the control group that did not use puzzle media. The average post-test score of the experimental group reached 80.71, while the control group was only 63.57. The t-test results show a significance value (2-tailed) of 0.000 <0.05, which means H0 is rejected and H1 is accepted. Thus, the use of educational puzzles is proven to have a positive effect on improving students' cognitive abilities on school rules material.